Merekonstruksi Evangelion dan Sosio-Kultural Misiologi: Upaya Menggempur Urban Society - Hesky Wauran; Stimson Hutagalung; Rolyana Ferinia (Jurnal Teologi Cultivation, 2022)
Abstract:Various evangelistic studies have focused on remote areas and paid less attention to urban communities. Jakarta as the capital city of Indonesia presents a heterogeneous society. One of the elements of society that has significance for the cultural and social formation in Jakarta is the community of Chinese descent. The Seventh-day Adventist Church (GMAHK) has a challenge to construct a contextual mission model in order to reach the Chinese community in Jakarta. By using descriptive qualitative methods and analysis, this study tries to formulate a contextual model that is contributive to the service of the Seventh-day Adventist Church's mission. In conclusion, the appropriate construction of contextual evangelism for the Seventh-day Adventist Church is to present Christ as the main foundation of truth and appreciate God's manifestations in the cultural practices and personal experiences of the Chinese community in Jakarta.Abstrak:Berbagai kajian penginjilan terpusat pada daerah-daerah pelosok dan kurang memberikan perhatian terhadap masyarakat perkotaan. Jakarta sebagai ibu kota Indonesia menampilkan masyarakat yang heterogenik. Salah satu elemen masyarakat yang memiliki signifikansi terhadap pembentukan budaya dan sosial di Jakarta adalah masyarakat keturunan Tionghoa. Gereja Masehi Advent Hari Ke-tujuh (GMAHK) memiliki tantangan untuk mengkonstruksikan model misi kontekstual dalam rangka menjangkau komunitas Tionghoa di Jakarta. Dengan menggunakan metode kualitatif deskriptif dan analisis, penelitian ini mencoba mengformulasikan model kontekstual yang kontributif bagi pelayanan misi GMAHK. Sebagai kesimpulan, konstruksi penginjilan kontekstual yang tepat bagi GMAHK adalah menampilkan Kristus sebagai landasan utama kebenaran dan menghargai manifestasi Allah pada praktik budaya dan pengalaman pribadi masyarakat Tionghoa di Jakarta.